Analisis Dan Perancangan Sistem Informasi Layanan Bimbingan Konseling Pada SMPN 17 Kabupaten Tebo - Dharmawangsa, Dharmawangsa; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2021)
Counseling services at SMPN 17 Tebo District have a short time. Therefore, a Web-based counseling service information system is required to assist the SMPN 17 Tebo district. A website is a form of technology development that can help in providing information without limited time. Counseling services designed to be presented in the form of a website can facilitate the management of student counseling data existing in the SMPN 17 Tebo district. The research uses the Unified Modelling Language (UML) modeling tool and generates a prototype that can be implemented into a system that can help manage the counseling service data at SMPN 17 Tebo district.